Teatro na formação do educador da infância: experiências e possibilidades - Simone Cintra; Ana Angélica Albano (EccoS – Revista Científica)
We present, in this article, aspects of a teacher training practice at the Faculty of Education at the University of Campinas (Unicamp), which was part of a doctoral research. This research is configured as a research-training to encompass the concomitant use of teacher training activities and research activities. The aspects discussed here refer to the experiences of the students, future teachers, with elements of drama. The dramatic games allowed the future teachers to experience daydream and the creative thinking charactistic of poetry. The whole process was recorded on audio and video. From the observation and analysis of the activities performed during the training process, we discussed the importance of creative experience as constitutive of the constant process of becoming an educator. Studies on drama and on education through the arts directed these reflections.